Description of the Self-Transformation of Drug Addicts During Active Recovery: The Role of Community Support - Nina Marlina; Adellya Saputri Ovian Oktaniasih; Alifia Ulie Mizana Hadori (Sahabat Publikasi, 2026)
Drug addiction recovery is not simply quitting substance use but a process of self-transformation that includes changes in social identity, internal motivation, and interpersonal relationships. This study aims to explore the subjective experiences of individuals in active recovery in DKI Jakarta. The approach used is qualitative with the Interpretative Phenomenological Analysis (IPA) method. Participants consisted of three informants, namely one adult drug addict (D-43) who had been in active recovery for 8 years, living with HIV, and involved in a support community; one family member (M-69); as well as two peer counselors (BM-48 and R-45). Data were collected through semi-structured interviews and field notes, then analyzed through repeated reading, theme development, and interpretation of meaning in a psychosocial context. The results of the study identified five main themes: (1) addiction as a chronic disease recurrence, (2) identity reconstruction through social roles, (3) community as a safe space and space of meaning, (4) crucial dynamics in active recovery, and (5) recovery capital. Recovery is interpreted as a non-linear process that requires awareness of the risk of recurrence and the formation of a new identity through social contribution. This process is influenced by internal factors such as willingness, honesty, and commitment, as well as external factors such as family support, economic stability, and access to health services. The findings confirm that the sustainability of recovery depends not only on individual motivation but also on the availability of recovery capital that supports holistic, sustainable, and relational self-transformation.